2018
DOI: 10.3390/nu10020205
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality of School Meals in France: Impact of Guidelines and the Role of Protein Dishes

Abstract: In France, school meals must comply with 15 frequency criteria (FC) expressed as nutritional requirements (e.g., “starters containing more than 15% fat served no more than four times out of 20”) in a series of 20 consecutive meals. The objective was to assess, for the first time, the nutritional impact of complying with French school food FC. Based on 40 series of meals actually served in primary schools (“observed series”), several scenarios (1600 series per scenario) of compliance or non-compliance with FC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 26 publications
6
43
0
2
Order By: Relevance
“…Other dimensions of diet sustainability may also be conflicting. For example, a study on meals served in French primary schools showed that the nutritional quality of computersimulated series of meals deteriorated when protein dishes were reduced or when meat−/fish-based dishes were replaced by vegetarian dishes [45]. These findings support research showing that nutritional adequacy can be compromised when animal products in diets are replaced with plant-based foods without properly considering nutritional aspects [46].…”
Section: Discussionmentioning
confidence: 69%
“…Other dimensions of diet sustainability may also be conflicting. For example, a study on meals served in French primary schools showed that the nutritional quality of computersimulated series of meals deteriorated when protein dishes were reduced or when meat−/fish-based dishes were replaced by vegetarian dishes [45]. These findings support research showing that nutritional adequacy can be compromised when animal products in diets are replaced with plant-based foods without properly considering nutritional aspects [46].…”
Section: Discussionmentioning
confidence: 69%
“…A complete dish is a dish where the protein “dish” and the side “dish” are incorporated into the same main dish (e.g., lasagne, gratins, chili con carne, etc.) An existing database, based on technical files for all dishes from 40 series of 20 meals, was available thanks to the previous study by Vieux et al [ 19 ] This previous database also contained 40 additional vegetarian dishes (complete dishes, protein dishes and side dishes). All complete dishes and protein dishes were extracted from this database ( n = 683).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study on French school meals [ 19 ] suggested that the systematic substitution of meat and fish with vegetarian dishes would have a detrimental impact with regard to several indicators of nutritional quality. The data for this previous study had been collected in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…As regards breakfast and nutrient balance they cite a cross-sectional survey of the Bogalusa Heart Study ( n = 504; 58% women; 70% white; mean age, 23 years [range, 19–28 years]) which demonstrated that 74% of breakfast skippers did not meet two thirds of the Recommended Dietary Allowance for vitamins and minerals compared with 41% of those who consumed breakfast. They also cite US data showing that young adults (age, 20–39 years) who reported skipping breakfast had overall daily diets that were less than optimal in terms of nutrient intake as measured by indices of total daily diet quality (Mean Adequacy Ratio, MAR and Healthy Eating Index HEI) [ 6 , 7 ]. Taking into account the direct evidence linking breakfast intake both to overall dietary patterns and the presence of cardio-metabolic risk factors, the statement concludes: “On the basis of the combined epidemiological and clinical intervention data, daily breakfast consumption among US adults may decrease the risk of adverse effects related to glucose and insulin metabolism.…”
Section: Existing Recommendations On Breakfast Consumptionmentioning
confidence: 99%